Nanosecond soliton pulse generation by mode-locked erbium-doped fiber laser using single-walled carbon-nanotube-based saturable absorber - Ismail, Mohd Afiq; Harun, Sulaiman Wadi; Zulkepely, Nurul Rozullyah; Nor, Roslan Md; Ahmad, Fauzan; Ahmad, Harith (Optical Society of America, 2012)
We demonstrate a simple and low cost mode-locked erbium-doped fiber laser (EDFL) operating in the nanosecond region using a single-walled carbon nanotube (SWCNT)-based saturable absorber (SA). A droplet of SWCNT solution is applied on the end of a fiber ferrule, which is then mated to another clean connector ferrule to construct an SA. Then the SA is integrated into a ring EDFL cavity for nanosecond pulse generation. The EDFL operates at around 1570.4 nm, with a soliton-like spectrum with small Kelly sidebands, which confirms the attainment of the anomalous dispersion. It produces a soliton pulse train with a 332 ns width, repetition rate of 909.1 kHz, an average output power of 0.31 mW, and energy of 0.34 nJ at the maximum pump power of 130.8 mW. (C) 2012 Optical Society of America